Psychological abuse and its influencing factors among home-dwelling older people in Northern China: a cross-sectional survey - Xiaomeng Wu; Li Pei; Yu Wang; Lanrui Zhang; Dongqing Zhao; Haoying Dou (Frontiers in Medicine)
BackgroundAs the population ages, the subject of elder abuse has become more prominent, with psychological abuse of older people being particularly prevalent. This leads to a higher incidence of anxiety, depression, and other psychological problems among older people, reducing their quality of life, and even jeopardizing their safety.MethodsA cross-sectional questionnaire survey was conducted to investigate psychological abuse among home-dwelling older people in Northern China and its influencing factors. Participants were surveyed using a demographic questionnaire, activities of daily living (ADL), family adaptability and cohesion evaluation scale (FACES), and elder psychological abuse scale. The factors impacting psychological abuse were examined using binary logistic regression.ResultsA total of 465 home-dwelling older people participated in the study, with an effective response rate of 97.89%. The median item score of psychological abuse was 20 (IQR: 18–22), activities of daily living was 15 (IQR: 14–17), and family adaptability and cohesion was 96 (IQR: 86–105). Binary logistic regression analysis indicated that the factors affecting psychological abuse among home-dwelling older people were residence in rural areas (OR = 3.487, 95% CI = 2.121–5.732), monthly income ≥ 3,501 (OR = 0.342, 95% CI = 0.119–0.987), had chronic diseases (OR = 2.202, 95% CI = 1.356–3.576), and FACES (OR = 0.955, 95% CI = 0.936–0.974) were the factors that influenced the prevalence of psychological abuse.ConclusionIn Northern China, the level of psychological abuse among older people is low. It is associated with residence, monthly income, chronic diseases, and family adaptability and cohesion. Further studies are required to understand the underlying causes and develop effective interventions to reduce psychological abuse and ensure a comfortable old life for older Chinese people.